2019
DOI: 10.17507/jltr.1001.06
|View full text |Cite
|
Sign up to set email alerts
|

Using Karaoke Videos to Teach Japanese Vocabulary to Taiwanese University Students

Abstract: This paper reports the usage of Japanese karaoke films in order to enhance learning Japanese vocabulary among students in a university in Taiwan. A pretest-posttest control-group design was implemented in which the treatment students (55 girls and 48 boys) were given Japanese vocabulary lessons via listening to and watching two karaoke films, while the control group (62 girls and 47 boys) received their Japanese vocabulary lessons through only listening to the same songs (N=212, P ≤ 0.05). The treatment lasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This research highlights the importance of using songs as an engaging and fun learning tool for students. Research by (Chang, 2019) found that vocabulary learning through songs can significantly improve students' vocabulary comprehension. The results of this study suggest that songs can be an effective resource for enriching the vocabulary of non-native speaker students.…”
Section: Diagram 1 the Effect Of Using English Song Lyricsmentioning
confidence: 99%
“…This research highlights the importance of using songs as an engaging and fun learning tool for students. Research by (Chang, 2019) found that vocabulary learning through songs can significantly improve students' vocabulary comprehension. The results of this study suggest that songs can be an effective resource for enriching the vocabulary of non-native speaker students.…”
Section: Diagram 1 the Effect Of Using English Song Lyricsmentioning
confidence: 99%